2018
DOI: 10.1101/368605
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive analysis of immune evasion in breast cancer by single-cell RNA-seq

et al.

Abstract: Abstract:The tumor microenvironment is composed of numerous cell types, including tumor, immune and stromal cells. Cancer cells interact with the tumor microenvironment to suppress anticancer immunity. In this study, we molecularly dissected the tumor microenvironment of breast cancer was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.The copyright holder for this preprint (which . http://dx.doi.org/10.1101/368605 doi: bioRxiv preprint first pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…As a first assessment, the 10cRNA-seq data were visualized by uniform manifold approximation and projection (UMAP) (37). Consistent with past descriptions of carcinoma heterogeneity by scRNA-seq (20,38,39), we found that 10cRNA-seq data clustered tightly by patient ( Fig. 2A).…”
Section: Crna-seq Transcriptomes Retain the Inter-tumor And Intra-tsupporting
confidence: 82%
See 2 more Smart Citations
“…As a first assessment, the 10cRNA-seq data were visualized by uniform manifold approximation and projection (UMAP) (37). Consistent with past descriptions of carcinoma heterogeneity by scRNA-seq (20,38,39), we found that 10cRNA-seq data clustered tightly by patient ( Fig. 2A).…”
Section: Crna-seq Transcriptomes Retain the Inter-tumor And Intra-tsupporting
confidence: 82%
“…scRNA-seq of dissociated tumors has identified (partial-)EMT states in some carcinomas (41,42) but not others (55). EMT-like transcriptional profiles also arise normally in the cell type of origin for serous ovarian cancer (56).…”
Section: Rhegs Are Enriched For Emt Signatures and Correlate With Canmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous analytical methods are categorized within this approach [23, 24, 2634, 36, 40, 4346, 48, 49, 51, 52, 55].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several studies investigated the tumor microenvironment of breast cancer. 23 , 24 The tumor microenvironment could be involved in paracrine interactions with malignant cells, leading to evading the immune surveillance and tumor progression. In this study, we focused on the malignant epithelial cells for network construction and revealed the essential roles of the critical genes.…”
Section: Discussionmentioning
confidence: 99%